2007
DOI: 10.1021/ic061196s
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Studies of a New Unsymmetrical κ4-PNN‘N‘ ‘-Tetradentate Ligand:  Stepwise Formation and Structural Characterization

Abstract: The two-step synthesis of a new unsymmetrical ligand 2-[Ph2PC6H4C(H)=N]C6H4[N(H)COCH2N(H)CO2Bz], 2.HH, via acid-catalyzed Schiff base condensation of 2-(H2N)C6H4[N(H)COCH2N(H)CO2Bz], 1, with 2-Ph2PC6H4(CHO) in refluxing EtOH is reported. The multidentate ligand 2.HH, isolated in ca. 60% yield, exhibits an array of ligation modes, as exemplified by coordination studies with NiII, PdII, PtII, and AuI mononuclear metal precursors. Hence, reaction of 2.HH with AuCl(tht) (1:1 molar ratio, tht = tetrahydrothiophene)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…Yield 0.104 g, 66 %. 1 A similar procedure was also used for the preparation of the rhodium(III) and iridium(III) complexes 11 (78 %) and 12 (35 %) respec- X-ray Crystallography: Measurements were made with either a Bruker AXS SMART 1000 CCD area-detector diffractometer [45] for 3·CHCl 3 , 4, 5, 7·CHCl 3 , 10·CH 2 Cl 2 ·0.5C 4 H 10 O and 13·2CH 2 Cl 2 using sealed-tube graphite-monochromated Mo-K α radiation and narrow frame exposures (0.3°) in ω or a Bruker-Nonius 95 mm CCD kappa diffractometer [46,47] equipped with a rotating anode generator for 4. Cell parameters were refined from the observed (ω) angles of all strong reflections in each data set.…”
Section: Preparation Of Cis-[pt(chmentioning
confidence: 99%
See 1 more Smart Citation
“…Yield 0.104 g, 66 %. 1 A similar procedure was also used for the preparation of the rhodium(III) and iridium(III) complexes 11 (78 %) and 12 (35 %) respec- X-ray Crystallography: Measurements were made with either a Bruker AXS SMART 1000 CCD area-detector diffractometer [45] for 3·CHCl 3 , 4, 5, 7·CHCl 3 , 10·CH 2 Cl 2 ·0.5C 4 H 10 O and 13·2CH 2 Cl 2 using sealed-tube graphite-monochromated Mo-K α radiation and narrow frame exposures (0.3°) in ω or a Bruker-Nonius 95 mm CCD kappa diffractometer [46,47] equipped with a rotating anode generator for 4. Cell parameters were refined from the observed (ω) angles of all strong reflections in each data set.…”
Section: Preparation Of Cis-[pt(chmentioning
confidence: 99%
“…As part of continuing studies [1][2][3][4][5][6] in our group we are interested in developing new tertiary and symmetric ditertiary phosphane ligands using simple condensation reactions. We, and others, have found that ditertiary phosphanes such as those of general formula (R 2 PCH 2 ) 2 N(R) have interesting coordination properties [7,8] including their use in selfassembly reactions through covalent bonds or H-bonding contacts.…”
Section: Introductionmentioning
confidence: 99%
“…2b,c,3, 4 We recently described a readily synthesised PNN¢N¢¢-tetradentate ligand and its diverse bonding capabilities to a range of late transition-metals. 5 Fluorene, diazofluorene or fluorenone groups have been used in organic synthesis 6 and for the preparation of metal complexes 7 including organometallic acetylides, 8 oligomers 9 and polymers. 10 However examples of monodentate or bidentate phosphine ligands bearing one or two fluorene groups are sparsely documented in the literature.…”
mentioning
confidence: 99%
“…This flexibility in ligand geometry mirrors our previous studies with a P/N/NЈ/NЈЈ-tetradentate system which likewise can adopt numerous coordination motifs. [25] The amide functional groups adopt various secondary hydrogen-bonding interactions and in solution, we believe some of these compounds exist as conformers due to hindered amide-bond rotation. Further studies are in progress and will be reported in due course.…”
Section: Discussionmentioning
confidence: 99%
“…This finding contrasts with the X-ray crystal structure of 2-{Ph 2 PC 6 H 4 C(H)=N}C 6 H 4 {NHC(O)CH 2 NHCO 2 -Bz}, recently reported by us, in which the -PPh 2 group points away from the N 3 core. [25] The hydrogen H(1) forms an intramolecular hydrogen bond to N (2) …”
Section: Thementioning
confidence: 99%